The effect of morphine upon DNA methylation in ten regions of the rat brain. Issue 12 (2nd December 2017) - Barrow, Timothy M.; Byun, Hyang-Min; Li, Xinyan; Smart, Chris; Wang, Yong-Xiang; Zhang, Yacong; Baccarelli, Andrea A.; Guo, Liqiong
ABSTRACT: Morphine is one of the most effective analgesics in medicine. However, its use is associated with the development of tolerance and dependence. Recent studies demonstrating epigenetic changes in the brain after exposure to opiates have provided insight into mechanisms possibly underlying addiction. In this study, we sought to identify epigenetic changes in ten regions of the rat brain following acute and chronic morphine exposure. We analyzed DNA methylation of six nuclear-encoded genes implicated in brain function ( Bdnf, Comt, Il1b, Il6, Nr3c1, and Tnf ) and three mitochondrially-encoded genes ( Mtco1, Mtco2, and Mtco3 ), and measured global 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5 hmC) levels. We observed differential methylation of Bdnf and Il6 in the pons, Nr3c1 in the cerebellum, and Il1b in the hippocampus in response to acute morphine exposure (all P value < 0.05). Chronic exposure was associated with differential methylation of Bdnf and Comt in the pons, Nr3c1 in the hippocampus and Il1b in the medulla oblongata (all P value < 0.05). Global 5mC levels significantly decreased in the superior colliculus following both acute and chronic morphine exposure, and increased in the hypothalamus following chronic exposure. Chronic exposure was also associated with significantly increased global 5hmC levels in the cerebral cortex, hippocampus, and hypothalamus, but significantly decreased in the midbrain. Our results demonstrate, for the first time, highly localized epigenetic changes in the rat brain following acute and chronic morphine exposure. Further work is required to elucidate the potential role of these changes in the formation of tolerance and dependence.